(untitled) (Research, Society and Development, 2021)
The present research aims to identify the positive and/or negative impacts resulting from the implementation of a Sewage Treatment Plant (STP) from the perspective of the surrounding community in the municipality of Sumé, Paraíba. To this end, the STP was chosen for its relevance in the social/local scenario, since this enterprise has the potential to generate social and environmental impacts. The study area was delimited considering the radius of 1 km around the STP, in order to characterize the number of residences that make up the neighborhood. The residences evaluated are located at different strategic points, as a way to ascertain their influence on the interviewees’ conception according to the place where they live. After delimiting the study’s area of coverage, it was possible to apply the questionnaire in the form of a semi-structured interview with the community around the STP, in order to serve as an instrument to assess the perception of the population about the social and environmental impacts caused by this enterprise. The data were tabulated in Excel 2019® spreadsheet and analyzed qualitatively and quantitatively. According to the results obtained, 70% of the interviewees indicated that the STP presented negative impacts, such as: increase in the proliferation of insects, bad smell, and a higher incidence of diseases in the areas close to the STP. In this sense, the implementation of the STP brought negative impacts on the socio-environmental sphere, and the degree of proximity of the respondents’ homes to the STP was crucial in the classification of these impacts.